Corruption, Corporations, and the New Human Right - Andrew B Spalding (Washington University Law Review, 2014)
We should no longer expect the Alien Tort Statute to be the principal federal statute that deters overseas corporate rights violations. That distinction rightly belongs to the Foreign Corrupt Practices Act, an anti-bribery statute that rests on undisputed principles of corporate liability, contains a clear congressional statement of extraterritorial application, and routinely collects penalties from multinational corporate defendants. Scholars have not associated the FCPA with human rights, owing principally to a thin understanding of rights theory. But freedom from corruption can and should be understood as a human right, one that is as old as social contract theory but new to federal and international law. With specific reforms—one modeled after environmental law and the other after intellectual property—the FCPA can become a more powerful statutory tool for deterring overseas corporate rights violations than the ATS ever was or will be.
Keywords: tort; Alien Tort Statute; Foreign Corrupt Practices Act; bribery; rights; corporate liability; extraterritorial application